Conception rate and body condition score at the time of artificial insemination in intensively reared Holstein cattle in a dairy farm in Lima - Cabrera O., Angélica (2022)
The study aimed to determine the effect of body condition score (SCC) at the time of artificial insemination on the conception rate (TC) of Holstein cows raised under an intensive system. In total, 1851 inseminations from dairy farm in Lima, Peru were evaluated. The SCC was evaluated through visual observation on a 1-5 scale, forming two groups: SCC <3 and SCC ≥3. The pregnancy diagnosis was made between days 35 and 42 post-service. Overall TC (GTC) and at first insemination were significantly higher in cows with SCC ≥3 than in cows with SCC <3 (p<0.01), with no significant differences at the second and third insemination. SCC had a significant effect on TC at first insemination in multiparous cows (p<0.05), but not in primiparous cows. The SCC did not have a significant effect on the GTC or at the first insemination in cows bred in times of heat stress (October-June), while the cows inseminated with SCC ≥3 during the thermal comfort season presented a better GTC and at the first insemination than those with SCC <3 (p<0.05). In conclusion, SCC at the time of artificial insemination has a significant effect on TC in cows reared in an intensive production system in Lima.